2011
DOI: 10.1007/s11869-011-0139-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the contribution of physical and chemical stressors to the daily number of hospital admissions implementing an artificial neural network model

Abstract: The relative contribution of chemical (air pollution) and physical (temperature and humidity) health stressors to urban hospitalization rates is the objective of the current study. The data used in the study included the daily number of hospital admissions due to cardiorespiratory diseases, hourly mean concentrations of CO, NO 2 , SO 2 , O 3 , and black smoke in several monitoring stations, as well as meteorological data (temperature, relative humidity, wind speed/direction) in Athens, Greece. The relations am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…The relationship between temperature and mortality and hospitalization has been shown to be non-linear (Nordio et al, 2015) and spline methods as well as Artificial Neural Networks (Kassomenos et al, 2011) methods to study the effect of non-linear parameters such as the temperature on cardiovascular admissions have been used.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between temperature and mortality and hospitalization has been shown to be non-linear (Nordio et al, 2015) and spline methods as well as Artificial Neural Networks (Kassomenos et al, 2011) methods to study the effect of non-linear parameters such as the temperature on cardiovascular admissions have been used.…”
Section: Introductionmentioning
confidence: 99%
“…PM long-term exposure was also associated with diabetes and cardiovascular and respiratory diseases (Martinelli et al, 2013), including atherosclerosis (Hoffmann et al, 2007), hypertensive episodes (Brook et al, 2007), arrhythmia (Rich et al, 2005) and asthma (Gehring et al, 2010). Kassomenos et al (2011) developed a neural network approach to estimate the significance of PM exposure in hospital admission for cardiovascular and respiratory diseases. The results for Athens showed that a 10 µg m −3 increase in PM 10 concentration led to an 8.6 % increase in hospitalizations .…”
Section: Particulate Matter and Healthmentioning
confidence: 99%
“…The analysis of national databases in the United States revealed higher mortality RRs for PM 2.5 exposure (Zanobetti and Schwartz, 2009). The APHEA project (Air Pollution and Health: a European Approach) investigated daily mortality data from 32 European cities and observed that mortality was associated with PM exposure: the daily mortality counts associated with 10 µg m −3 of PM 10 increased by 0.52 %, and it increased by 0.76 % and 0.71 % for cardiovascular and respiratory mortality, respectively (Analitis et al, 2006;Katsouyanni and Grp, 2006). The effects were more pronounced during the first and second day for total mortality and cardiovascular mortality, while respiratory mortality showed more prolonged lagged effects.…”
Section: Particulate Matter and Healthmentioning
confidence: 99%
“…ANN models are capable of fast processing with several input and output variables (Lal and Tripathy 2012;Kakosimos et al 2011;Bose and Liang 1998;Anderson 1995). ANN models have been very accurate in many environmental health application areas, especially indoor environment (Skön et al 2012;Kassomenos et al 2011), air quality forecasting Goyal and Kumar;Alekseev and Seixas Citation details: Patra, A., Gautam, S., Majumdar, S., . Prediction of particulate matter concentration profile in an opencast copper mine in India using an artificial neural network model.…”
Section: Introductionmentioning
confidence: 99%